Formative research to identify perceptions of e-cigarettes in college students: Implications for future health communication campaigns - Case, Kathleen (J Am Coll Health, 2016)
OBJECTIVE: This formative study examined perceptions of e-cigarettes in college students with the goal of informing future health communication campaigns. Differences between e-cigarette users and nonusers were also examined. Participants: Thirty undergraduate students were recruited from a large southwestern public university (15 users, 15 nonusers). METHODS: Structured interviews were conducted and transcripts were coded for themes. RESULTS: Although users had more favorable attitudes toward e-cigarettes, both users and nonusers believed that e-cigarettes produce water vapor and reported that e-cigarettes were less harmful than conventional cigarettes. Potential health consequences and addiction concerns were the most common perceived threats for both users and nonusers. Both nonusers and users cited social stigma as a perceived disadvantage of e-cigarette use. CONCLUSIONS: Ultimately, themes with particular relevance to future health communication campaigns included negative perceptions of e-cigarette users and social stigma, as well as harm perceptions and potential health consequences associated with e-cigarette use.